1988
DOI: 10.1093/nar/16.22.10861
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of methods for covalent binding of nucleic acids to magnetic beads, DynabeadsTM, and the characteristics of the bound nucleic acids in hybridization reactions

Abstract: Dynabeads are magnetic monosized beads with high stability, high uniformity, unique paramagnetic properties, low particle-particle interaction, and high dispersibility. Different reactive groups; hydroxyl, carboxyl and amino groups can be attached to the surface. Several methods for covalent attachment of DNA or oligonucleotides to the beads were investigated. Best coupling yields were obtained by carbodiimide-mediated end-attachment of 5'-phosphate and 5'-NH2 modified nucleic acids to respectively amino and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0
4

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 16 publications
2
54
0
4
Order By: Relevance
“…Therefore, very often functional/active groups are introduced to either the 3Ј-end or 5Ј-end of oligonucleotides and solid supports to allow end-specific immobilization. However, these functional groups often cause a high degree of nonspecific binding during attachment (9,17,26) and even hybridization (26). For example, it has been reported that nonspecific attachment and nonspecific hybridization of oligonucleotides occurs on both aminosilane-modified (9) and epoxysilane-modified (26) surfaces, which are the two most commonly used silane-modified surfaces for DNA array preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, very often functional/active groups are introduced to either the 3Ј-end or 5Ј-end of oligonucleotides and solid supports to allow end-specific immobilization. However, these functional groups often cause a high degree of nonspecific binding during attachment (9,17,26) and even hybridization (26). For example, it has been reported that nonspecific attachment and nonspecific hybridization of oligonucleotides occurs on both aminosilane-modified (9) and epoxysilane-modified (26) surfaces, which are the two most commonly used silane-modified surfaces for DNA array preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Covalent coupling is the most popular approach for immobilization of biomolecules. The solution-based binding kinetics has been extensively studied, making the coupling approach available for different applications [42,43]. Covalently coupled, probes are favorably presented on the surface of the bead, leaving the binding moieties available for interaction with target molecules.…”
Section: Surface Functionalization Of Microbeadsmentioning
confidence: 99%
“…In a much earlier attempt to solve this problem, Lund et al (5) reported end-attachment of restricted DNA to a carboxylated magnetic beads using carbodiimide reagent at pH 7. The 5Ј-end of the DNA had been modified by attachment of a ␤-amino alkyl substituent, so attachment to the beads via an amide bond was assumed.…”
mentioning
confidence: 99%